Policy rules and forward guidance following the Covid-19 recession - Papell, David H.; Prodan-Boul, Ruxandra (Journal of Financial Stability, 2024)
In August 2020, the Federal Open Market Committee adopted a far-reaching Revised Statement on Longer-Run Goals and Monetary Policy Strategy. The framework contains two major changes from the original 2012 statement. First, policy decisions will attempt to mitigate shortfalls, rather than deviations, of employment from its maximum level. Second, the FOMC will implement Flexible Average Inflation Targeting. We show how to modify the rules in the Fed’s Monetary Policy Report to be consistent with the revised statement, how the pattern of falling behind the curve, pivot, and getting back on track in Fed policy during 2021 and 2022 could have been avoided by following inertial rules consistent with either the original or the revised statements, and how current and projected Fed policy for 2023 – 2026 is in accord with the prescriptions from inertial rules.